Facebook addiction among Rajshahi university students: A Cross-sectional study - Md. Al Mamun, Abu Sayed; Mamun, Jannatul Nayem; Farhana Hasan; Md. Golam Hossain (Thai Social Science Journal, 2026)
Background: Social media platforms like Facebook have become integral to students’ daily routines, offering opportunities for communication, academic collaboration, and social interaction. However, their excessive use can negatively influence academic performance, disrupt time management, and contribute to mental health challenges. This study investigates the prevalence and associated factors of Facebook addiction among students at Rajshahi University in Bangladesh. Method: Utilizing a cross-sectional design, data were collected from 400 randomly selected students residing in both male and female university halls. The research employed a structured, pre-tested questionnaire incorporating the Bergen Facebook Addiction Scale (BFAS) to categorize students into three addiction levels: not addicted, mildly addicted, and addicted. Analytical tools included descriptive statistics, graphical representations, Chi-square tests, and multinomial logistic regression. Results: The findings revealed that 28.25% of students were classified as addicted, 53.50% were mildly addicted, and the remaining 18.25% were not addicted. Moreover, male students were significantly more prone to Facebook addiction than female students. In addition, students with lower GPAs were more likely to be moderately or severely addicted. Furthermore, students whose mothers had lower levels of education exhibited higher levels of addiction. Interestingly, students from joint families experienced a lower risk of moderate addiction compared to those from nuclear families. The study also identified behavioral factors such as the duration of Facebook use and the number of online friends as strong predictors of addiction. Conclusion: In conclusion, the results showed that Facebook addiction among students is affected by academic, family, and behavioral factors. To deal with this problem, the university authorities and the government of Bangladesh should take steps such as offering digital literacy programs, providing counseling services, and encouraging family involvement to help students use social media in a healthier way.